[Rezension von: Carey, Holly J., Women who do : female disciples in the gospels] - Ma, Tianji 1987-; Carey, Holly J. (2025)
Holly Carey examines the role of women as disciples in the New Testament, arguing that they exemplify true discipleship through faithfulness and action. She explores the Gospels and Acts, demonstrating that women consistently model commitment to Jesus, often in contrast to the failures of the Twelve. Using historical, social and narrative-critical approaches, she reveals how these women actively shaped early Christian communities. While highlighting key strengths, the review also critiques aspects of her comparative analysis. This work is essential for biblical scholars, pastors and anyone interested in reexamining the role of women in Christian discipleship.
Keywords: Rezension